Determination of Ash Values of Two Endangered - Kadam V.B2, Tambe S.S.1* and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US;">The seasonal variation of total ash, acid soluble ash and acid insoluble ash have been investigated in leaves, stem and bark, of Madhuca indica and Butea monosperma which are medicinally important taxa in Marathwada region. Comparative account of total ash content of stem of Butea monosperma showed high level ( range 14.65 % to 16.5 %) than total ash content of stem of Madhuca indica ( range 7.3 % to 8.6 %). Acid soluble ash content of leaves of Madhuca indica showed lower (range 6.5 % to 8.5 %) and higher in stem of Madhuca indica (range 11.3 % to 12.35 %) compare to other parts. Acid insoluble ash of bark of Madhuca indica (range 3.9 % to 5.45 %) showed high level and lower in bark of Butea monosperma (range 1.85 % to 2 %).